2007
DOI: 10.1007/s10834-007-9062-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting Group Long-Term Care Insurance Enrollment Decisions

Abstract: This paper examines factors that influence whether or not employees choose to enroll in a group long-term care insurance plan. A conceptual family decision-making framework is used to group factors to study the enrollment decision of 509 state employees who were offered a long-term care insurance plan in 2000. Logistic regression results revealed that employee age, perceived risk, perceived affordability, decision-making style (communication with others and use of information), goals of control and choice, goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 10 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…[15] In contrast, people who expect to rely on family members for care are less likely to purchase the insurance. [16]…”
mentioning
confidence: 99%
“…[15] In contrast, people who expect to rely on family members for care are less likely to purchase the insurance. [16]…”
mentioning
confidence: 99%
“…For example, an aging population may place greater importance on long-term care insurance, and such coverage is beginning to receive more attention in the literature (e.g. Schaber and Stum 2007). Extensions of research that address these study limitations should be beneficial in understanding a broader range of effects from changes to U.S. health policy.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have focused on understanding behaviors in regards to LTCI as one financing alternative (AARP 2009;AHIP 2007;Curry et al 2009;Cramer and Jensen 2006;Mellor 2000;MetLife Mature Market Institute 2009;Schaber and Stum 2007;Swamy 2004). Some studies have explored intentions as well as behaviors and found that the majority of individuals who did not purchase LTCI intended to buy LTCI in the future (AHIP 2007;Swamy 2004).…”
Section: Financial Ltc Planning Behaviorsmentioning
confidence: 99%
“…For example, deciding when to retire as a couple (Behringer et al 2005;Smith and Moen 2004) or where to live as a couple (Adams 2004) were often difficult decisions for couples to make because of spouses' varying intentions and behaviors and their challenge of finding consensus with their decisions (Skogrand et al 2011). Financial LTC planning strategies also involve varying perceptions of intentions and behaviors that couples must communicate and make a decision about (Schaber and Stum 2007). Second, this body of research consistently reflects that not all couples reached consensus with their decision behaviors.…”
Section: Decision-making Among Couplesmentioning
confidence: 99%
See 1 more Smart Citation